Asymptotic estimates for the best trigonometric and bilinear approximations of classes of functions of several variables - Romanyuk, A. S.; Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain exact order estimates for the best $M$-term trigonometric approximations of the Besov classes $B_{∞,θ}^r$ in the space $L_q$. We also determine the exact orders of the best bilinear approximations of the classes of functions of $2d$ variables generated by functions of d variables from the classes $B_{∞,θ}^r$ with the use of translation of arguments.